The Modern University’s Mission and Transformation: Addressing Challenges in a Multipolar World - Davletova, Ainash; Orazova, Nazerke; Renobell, Víctor; Khairullin, Rafael; Ponkratov, Vadim; Burmykina, Irina; Savenko, Natalya; Dudnik, Olesya (Emerging Science Journal, 2025)
In the modern higher education sphere, universities’ ability to adapt has become more vital to their success and longevity. This study investigates the influence of leadership, technological innovation, sociopolitical engagement, skill and curriculum development, institutional collaboration, and governmental regulatory frameworks on university adaptability. Quantitative research was conducted by surveying 980 participants from various institutions in Kazakhstan, Russia, and Spain, using a standardized questionnaire. Structural equation modeling was employed to analyze variable connections. The findings suggest that leadership (β = 0.32, p < 0.001), technological innovation (β = 0.28, p < 0.001), sociopolitical engagement (β = 0.19, p < 0.001), and curriculum and skills development (β = 0.25, p < 0.001) have a substantial positive impact on the adaptability of universities. Furthermore, the mediation analysis demonstrated that institutional collaboration partially mediated the relationship between university adaptability and both leadership (indirect effect = 0.14, p < 0.01) and technological innovation (indirect effect = 0.12, p < 0.01). Additionally, moderation analysis verified that the government regulation framework substantially moderated the effects of leadership (β = 0.15, p = 0.02) and technological innovation (β = 0.10, p = 0.03) on university adaptability. These findings emphasize the importance of new technologies, effective leadership, and institutional collaboration for improving university adaptability. Doi: 10.28991/ESJ-2025-09-01-022 Full Text: PDF